STUDY OF THE INFLUENCE OF AN EXTERNAL FACTOR - THE CONDITIONS OF A GENERAL PANDEMIC ON THE LEVEL OF CREDIT RISK OF RUSSIAN BANKS - V. Manuylenko; A. Deduk (Вестник Северо-Кавказского федерального университета, 2022)
In modern conditions, one of the external factors - the spread of coronavirus infection-negatively affects the functioning of banks, the real sector ofproduction, consumption, causing credit risk, manifested both in banks and in their borrowers-legal entities, individuals. The purpose of the study is to develop tools for studying the impact of an external factor - a general pandemic on the level of credit risks of Russian banks and to justify the directions of their regulation by the credit risk manager. The study expands the theoretical understanding of the essence of credit risk based on the factor approach, taking into account the influence of this external factor, identifies general changes in the composition and structure of the income of the Russian population - the main criterion that determines the magnitude of credit risks in the context of a general pandemic, identifies the main measures of credit risk management aimed at improving the quality of the loan portfolio and reducing the impact offluctuations in the income of the population in the context of a global pandemic.